2021
DOI: 10.1149/1945-7111/ac0e4d
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Control of Electrolyte Trapping Polysulfide for Enhanced Lithium-Sulfur Batteries

Abstract: Lithium sulfur (Li-S) batteries are considered one of the most promising energy storage devices due to their high specific capacity, pollution-free reactant, and low cost. However, the “shuttle effect” of lithium polysulfide (Li2S x ) leads to a fast capacity decay and poor cycle life. Here, the magnetorheological effect (MRE) is first applied in Li-S batteries and a magnetic control electrolyte is designed by introducing carbonyl iron powders (CIPs) to improve the performance of Li-S batteries. According to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…47 However, the introduction of magnetic-field into rechargeable batteries has recently become an attractive topic for boosting battery performance. Although some achievements have been made, for example, dendrite formation inhibition 18,19,21 and polysulfide shuttle effect mitigation, 48,49 the battery reaction mechanism and long-term stability under the coexistence of battery electric field and magnetic field have yet to be thoroughly studied and understood. An in-depth understanding of magnetic field effects and the challenges can lead to significant technological breakthroughs in magnetic field-assisted batteries.…”
Section: Magnetic Field-assisted Batteriesmentioning
confidence: 99%
See 3 more Smart Citations
“…47 However, the introduction of magnetic-field into rechargeable batteries has recently become an attractive topic for boosting battery performance. Although some achievements have been made, for example, dendrite formation inhibition 18,19,21 and polysulfide shuttle effect mitigation, 48,49 the battery reaction mechanism and long-term stability under the coexistence of battery electric field and magnetic field have yet to be thoroughly studied and understood. An in-depth understanding of magnetic field effects and the challenges can lead to significant technological breakthroughs in magnetic field-assisted batteries.…”
Section: Magnetic Field-assisted Batteriesmentioning
confidence: 99%
“…50 The MHD effect can promote the battery mass transfer process and facilitate the uniform shape of deposited morphology, thereby benefiting the battery performance with much-improved energy efficiency, capacity, and cycling stability. It is worth noting that in the reported magnetic field-assisted sulfur-based systems, 48,49,51 magnetic particles, such as Fe 2 O 3 and carbonyl iron, are typically used (Figure 3B). These magnetic particles, containing vacant electron d-orbital Fe atom, can form strong bonds with polysulfide species.…”
Section: Magnetic Field-assisted Batteriesmentioning
confidence: 99%
See 2 more Smart Citations
“…Pan et al reported that the adsorption free energy of H atoms (Δ G H* ) of bimetallic CoFe@N–C (−0.561 eV) is lower than that of Fe@N–C (−0.603 eV) and Co@N–C (−0.623 eV), which justifies the improvement in the HER activity . Previous works have demonstrated that the adsorption energy between lithium polysulfides (Li 2 S 4 ) and CoFe is −17.63 eV by DFT, which is much higher than that of single metals Co (−3.11 eV) and Fe (−2.68 eV) and other Co-based metallic alloys (CoNi: −4.24 eV). …”
Section: Introductionmentioning
confidence: 99%